2013
DOI: 10.5935/1808-8694.20130098
|View full text |Cite
|
Sign up to set email alerts
|

Auditory satisfaction of patients fitted with hearing aids in the Brazilian Public Health Service and benefits offered by the hearing aids

Abstract: The subjects included in the study have benefitted from being fitted with hearing aids and have been very happy with the outcome of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
(39 reference statements)
0
7
0
11
Order By: Relevance
“…The relationship between the use of a technological resource (HA or CI) and receptive vocabulary, demonstrated in this study reinforces the crucial role of hearing recovery in the maintenance of auditory experiences, being a determinant factor for the lower participation restriction (26,27) . However, only the technological resource is not sufficient to ensure a good performance in the vocabulary.…”
Section: Discussionmentioning
confidence: 67%
“…The relationship between the use of a technological resource (HA or CI) and receptive vocabulary, demonstrated in this study reinforces the crucial role of hearing recovery in the maintenance of auditory experiences, being a determinant factor for the lower participation restriction (26,27) . However, only the technological resource is not sufficient to ensure a good performance in the vocabulary.…”
Section: Discussionmentioning
confidence: 67%
“…Also showed the importance of the individual monitoring, because it found that the aspects related to the subscale negative factors the effective use of amplification during the acclimatization period further increased the satisfaction. It is worth mentioning the importance of regular monitoring of the hearing aid user, even after it has been adapted and also the counseling sessions to work issues to the expectations of patients and families, as well as the difficulties presented in challenging situations 36 In the national literature can be found studies 17,37 that link high level of satisfaction in patients who received their hearing aids through the dispensation of the Unified Health System. This study also showed high satisfaction in individuals who acquired their devices in a private service.…”
mentioning
confidence: 99%
“…They also reported that satisfaction was not related to the variables gender, age, degree of hearing loss and profile electroacustic 11 . In Brazilian literature there are several studies on the satisfaction of hearing aid users who are accompanied in public services, but little is read on patients treated in private services, such as the auditives centers 5,11,12 . US researchers conducted a study comparing hearing aid users attending a private service and users of public services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indivíduo Sexo Idade (anos) Quais são os aspectos negativos em relação ao atendimento pela internet? (Cox e Alexander, 1999;Farias e Russo, 2010;Magalhães e Mondelli, 2011;Laperuta e Fiorini, 2012;Aurélio et al, 2012;Silva et al, 2013;Dell`Antonia et al, 2013;Bento et al, 2015;Almeida et al, 2016).…”
Section: Objetivos Secundáriosunclassified